2022
DOI: 10.3389/fneur.2022.964017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of falls, vestibular multimodal processing, and multisensory integration decline in the elderly–Predictive role of the functional head impulse test

Abstract: Age-related degeneration of the vestibular system, also known as presbyastasis, leads to unstable gait and higher risk of falls. These conditions affect lifestyle and may have non-negligible social repercussions due to fear-related states of anxiety and depression. In order to develop a model for predicting risk of falls, we assessed vestibulo-ocular function by video and functional Head Impulse Tests (vHIT and fHIT) and their possible correlations with Tinetti Balance Test score. Thirty-one patients over 65 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…The test evaluates the ability to accurately recognize a picture that is quickly displayed during VOR activation. A recent study demonstrated that, when the multisensory integration deteriorates (i.e., fHIT scores lower than 80%), the risk of fall increases 3.9 times [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The test evaluates the ability to accurately recognize a picture that is quickly displayed during VOR activation. A recent study demonstrated that, when the multisensory integration deteriorates (i.e., fHIT scores lower than 80%), the risk of fall increases 3.9 times [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While normal findings are obtained with vHIT, abnormal results may be seen with fHIT. The most likely reason for it is that the identification of the C optotype presented in fHIT depends not only on an intact VOR but also on the integration of vestibular, visual and cortical information 17 and therefore it is likely to be less specific for vestibular abnormalities. Moreover, ocular abnormalities can affect test results in fHIT.…”
Section: Discussionmentioning
confidence: 99%
“…Düşme hikâyesi olmayan grupta adaptasyon skorlarının daha iyi olduğu görüldü. 19 Soto-Varela ve ark.nın yapmış olduğu çalışmada son bir yıl içinde en az bir kez düşmüş yaşlı bireylerle düşme hikâyesi olmayan yaşlı bireylerin Duyu Organizasyon Testi (DOT) ve DEÖ skorları karşılaştırılmıştır. 13 Düşmüş olanlar, Koşul 2'de (p=0,043) ve somatosensöriyel bilgi kullanımında (p=0,039) düşmeyenlere göre daha kötü skorlar elde etmiştir.…”
Section: Bulgularunclassified